The Determinants of Bank Profitability in Vietnam during the period 2009-2015 - LUU, HANH THU (2016)
This paper analyses unemployment and GDP growth as prospective macroeconomic determinants together with economies of scale, capital adequacy, non-interest income activities, interbank funding, earnings stability, cost efficiency and risk management including credit, liquidity and insolvency risks as prospective bank-specific determinants of bank performance in Vietnam. A panel data comprising 42 commercial banks from 2009- 2015 is examined. I employ a dynamic two-stage SGMM approach to run regression on ROAA following two models: one with loan loss provisions and the other with interbank ratio to capture these crucial features of the Vietnamese banking industry while ensuring the validity of the econometric model. X-efficiency scores for banks are obtained in the first stage using SFA approach before incorporated in the SGMM model as an endogenous independent variable. Empirical results suggest that liquidity, earnings stability, interbank funding and cost efficiency significantly positively affect profitability whilst an adverse impact is significant for non-interest income, capital adequacy, credit risk and insolvency risk. Interestingly, bank profit is positively influenced by unemployment and their relationship is significant in LLP model.